Longitudinal evaluation of PROMIS-29 and FACIT-dyspnea short forms in systemic sclerosis. - Hinchcliff, Monique E; Beaumont, Jennifer L; Carns, Mary A; Podlusky, Sofia; Thavarajah, Krishna; Varga, John; Cella, David; Chang, Rowland W (Journal of Rheumatology, 2015)
Objective: To assess the sensitivity of the Patient-Reported Outcomes Measurement Information System 29-item Health Profile (PROMIS-29) and the Functional Assessment of Chronic Illness Therapy-Dyspnea 10-item short form (FACIT-Dyspnea) for measuring change in health status and dyspnea in systemic sclerosis (SSc).Methods: One hundred patients with SSc completed the PROMIS-29, FACIT-Dyspnea, and traditional instruments [Medical Research Council Dyspnea Score, St. George's Respiratory Questionnaire (SGRQ), Health Assessment Questionnaire-Disability Index (HAQ-DI), and Medical Outcomes Study Short Form-36 (SF-36)] at baseline and 1-year visits. PROMIS-29, FACIT-Dyspnea, and traditional instrument change scores were compared across composite modified Medsger Disease Severity and modified Rodnan Skin score (mRSS) change groups.Results: Moderately high Spearman correlation coefficients were observed between FACIT-Dyspnea and SGRQ (r = 0.57), FACIT-Dyspnea functional limitations and SF-36 physical component summary (PCS; r = 0.51), PROMIS-29 physical functioning and HAQ-DI (r = 0.50), and SF-36 PCS (r = 0.52) change scores. In most validity comparisons, PROMIS-29, FACIT-Dyspnea, HAQ-DI, and SF-36 scores performed similarly. While PROMIS-29 covers more content areas than SF-36 (e.g., sleep), it may do so at the expense of responsiveness of its 4-item physical function scale as compared to the multiitem-derived SF-36 PCS. Statistically significant increases in SF-36 role physical (p = 0.01) and physical component scale (p = 0.016), but not PROMIS-29, were observed in patients with mRSS improvement.Conclusion: PROMIS-29 and FACIT-Dyspnea are valid instruments to measure health status and dyspnea in patients with SSc. In physical function assessment, longer PROMIS short forms or computer adaptive testing should be considered to improve responsiveness to the effect of skin disease changes on physical function in patients with SSc.